Characteristics of core refractive index axial asymmetry LPFGs written by femtosecond laser. (1st January 2012) - Sun, Xiaoyan; Liu, Lei; Hu, Youwang; Duan, Jian; Liao, Ping; Zhu, Xiaonong
Direct writing of long period fibre gratings (LPFGs) in standard single mode fibres (SMF) with infrared femtosecond laser pulses is experimentally investigated. It is found that the transmission spectra of LPFGs can be controlled by infrared femtosecond laser focus condition. The transmission spectra of LPFGs present single resonance peak when the microscopic objective is 25´, which is distinct from the LPFGs manufactured by UV laser irradiation with mask. However, when the microscopic objective is 10´, the LPFGs transmission spectra with four rejection bands can be obtained. When the distribution of femtosecond laser energy is changed by inserting a diaphragm, the LPFGs transmission spectra present multi resonance peaks.